EFEKTIFITAS PENERAPAN MEDIA PEMBELAJARAN BOARDGAME UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Ananda Muazizah; Rita Ningsih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The learning methods applied by teachers have a big influence on their students. Teachers often provide learning methods to students using the lecture method, where students often feel bored in learning, especially mathematics. Given the problems in mathematics learning, teachers must be creative to increase students' enthusiasm for carrying out mathematics learning, using board game-based learning media. The development of game media in learning is very rapid for every teaching staff to follow advances in game-based technology for mathematical problem solving abilities. This research aims to determine the effectiveness of applying Board Game learning media to improve mathematical problem solving abilities. The method used by researchers is the SLR (Systematic Literature Review) method. With data collection techniques by documenting and reviewing 10 articles related to Board Game learning media and 10 articles related to mathematical problem solving from articles for 2018-2024. The articles used in this research were 20 national journal articles obtained from Google Scholar. From most of the studies in this article, researchers can conclude that board game learning media can help students improve their mathematical problem solving abilities.